2021
DOI: 10.3390/ma14154127
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Fracture Toughness and Impact Strength of PMMA Reinforced with Nano-Particles and Fibre as Advanced Denture Base Materials

Abstract: Statement of Problem: Polymethyl methacrylate (PMMA) denture resins commonly fracture as a result of the denture being dropped or when in use due to heavy occlusal forces. Purpose: To investigate the effects of E-glass fibre, ZrO2 and TiO2 nanoparticles at different concentrations on the fracture toughness and impact strength of PMMA denture base. Materials and Methods: To evaluate fracture toughness (dimensions: 40 × 8 × 4 mm3; n = 10/group) and impact strength (dimensions: 80 × 10 × 4 mm3; n = 12/group), 286… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 51 publications
5
30
0
Order By: Relevance
“…An additional explanation could be that the use of a silane coupling agent promoted better bonds between the glass fibre/ZrO 2 nanoparticles and the polymer matrix [6,38]. This was supported by the SEM images in the previous work, which confirmed that little or no gap had formed around the fibres on the fracture surface of the E-glass fibres specimens [28,29].…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…An additional explanation could be that the use of a silane coupling agent promoted better bonds between the glass fibre/ZrO 2 nanoparticles and the polymer matrix [6,38]. This was supported by the SEM images in the previous work, which confirmed that little or no gap had formed around the fibres on the fracture surface of the E-glass fibres specimens [28,29].…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, 1.5 and 3.0 wt.% ZrO 2 and 1.5 wt.% TiO 2 , and all E-glass fibre concentrations significantly increased the fracture toughness of the PMMA. Incorporating ZrO 2 or TiO 2 nanoparticles at any concentration did not enhance the impact strength of the PMMA, but adding 3.0, 5.0, and 7.0 wt.% of E-glass fibres did significantly increased the impact strength [29].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations